2021
DOI: 10.3390/diagnostics11040700
|View full text |Cite
|
Sign up to set email alerts
|

Nucleic Acid-Based Lateral Flow Biosensor for Salmonella Typhi and Salmonella Paratyphi: A Detection in Stool Samples of Suspected Carriers

Abstract: A multiplex rapid detection system, based on a PCR-lateral flow biosensor (mPCR-LFB) was developed to identify Salmonella Typhi and Salmonella Paratyphi A from suspected carriers. The lower detection limit for S. Typhi and S. Paratyphi A was 0.16 and 0.08 ng DNA equivalent to 10 and 102 CFU/mL, respectively. Lateral flow biosensor was used for visual detection of mPCR amplicons (stgA, SPAint, ompC, internal amplification control) by labeling forward primers with fluorescein-isothiocyanate (FITC), Texas Red, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
(62 reference statements)
0
10
0
Order By: Relevance
“…This technique demonstrate a high potential for recognizing carriers among foodstuff handlers and suspected carriers, hence, additional validation studies have been merited. The LFNAA analysis of the mPCR‐LFB has demonstrated higher sensitivity and speed than the frequently used agarose gel electrophoresis (Amalina et al., 2021).…”
Section: Determination Of Pathogenic Bacteria Using Lfasmentioning
confidence: 99%
“…This technique demonstrate a high potential for recognizing carriers among foodstuff handlers and suspected carriers, hence, additional validation studies have been merited. The LFNAA analysis of the mPCR‐LFB has demonstrated higher sensitivity and speed than the frequently used agarose gel electrophoresis (Amalina et al., 2021).…”
Section: Determination Of Pathogenic Bacteria Using Lfasmentioning
confidence: 99%
“…Owing to the poor sensitivity of the blood culture method, which is dependent on the abilities and knowledge of the laboratory staff, patients with a negative blood culture in the control group bear the risk of including undetected Salmonella Typhi cases [ 47 ]. Polymerase chain reaction (PCR) seems to be a more suitable method for use as the reference standard, as several studies have reported that PCR is more sensitive than the culture method [ 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“… 30 and Salmonella spp. 31 Expert personnel or expensive equipment are no longer required; moreover, the results can be simply inspected by the naked eye. Thus, we aimed to develop a PCR-LFA based on the nucleotide signature of the rbc L region to detect Aristolochia, the plants responsible for aristolochic acid nephropathy.…”
Section: Introductionmentioning
confidence: 99%